2018
DOI: 10.1016/j.redox.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine attenuates systemic platelet activation and cerebral vessel thrombosis in diabetes

Abstract: ObjectiveWe previously demonstrated that diabetes exacerbates stroke-induced brain injury, and that this correlates with brain methylglyoxal (MG)-to-glutathione (GSH) status. Cerebral injury was reversed by N-acetylcysteine (NAC). Here we tested if the pro-thrombotic phenotype seen in the systemic circulation and brain during diabetes was associated with increased MG-glycation of proteins, and if NAC could reverse this.MethodsThe streptozotocin (STZ)-induced mouse model of type 1 diabetes was used. Thrombus fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 42 publications
(57 reference statements)
1
44
0
2
Order By: Relevance
“…4), which enhances its antithrombotic effect. In another study, the inhibiting action of N-acetylcysteine on platelet activation was found, which also results in the antithrombotic effect of that drug [22]. Our results show that N-acetylcysteine reduces the expression of PECAM1 in endothelial cells (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…4), which enhances its antithrombotic effect. In another study, the inhibiting action of N-acetylcysteine on platelet activation was found, which also results in the antithrombotic effect of that drug [22]. Our results show that N-acetylcysteine reduces the expression of PECAM1 in endothelial cells (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Although our data demonstrated that mitochondrial autophagy is a protective signal for LPS‐treated cardiomyocyte, there are several different findings for mitophagy. For example, excessive mitophagy seems to be an early feature of cardiomyocyte mitochondrial damage due to mitophagy‐mediated mitochondria clearance (Wang, Yee, & Stokes, ; Yang et al, ). Besides, in diabetic cardiomyopathy, mitophagy activation impairs cardiac function via affecting the balance of cellular calcium.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of N-acetylcysteine (NAC), a synthetic drug with antioxidant properties, in the treatment of diseases of the central nervous system is widely studied [13]. Experimental studies indicate the ability of NAC to detect cerebroprotective effects under DM conditions [14].…”
Section: Analysis Of Recent Studies and Publications In Which A Solutmentioning
confidence: 99%